Yusof Ishak : a man of many firsts - Ooi, Kee bang (Singapore : Yusof Ishak Institute, 2017)
In English
Keywords: Journalists -- Singapore -- Biography; Presidents -- Philippines -- Singapore; Presidents -- Singapore -- Pctorial qorks,.; Yusof bin Ishak, 1910-1970.; Yusof bin Ishak, 1910-1970 -- Pictorial works